076 Dexmedetomidine sedation to facilitate CT coronary angiography in children: a novel approach. (December 2018) - Morrison, C; Hepburn, L; Stuart, G
Abstract : Introduction: Dexmedetomidine has been proven to provide safe and reliable sedation in children and is a viable option for radiological imaging studies. No previous studies describe the use of Dexmedetomidine for CT coronary angiography, to provide safe sedation in combination with a relatively reduced heart rate in children who are at high risk of complications from general anaesthesia. Historically, in order to achieve ideal imaging conditions, heart rate control may have been achieved by pre-loading with oral long-acting beta-blockers over a few days or intravenous short-acting beta-blockade at the time of anaesthesia. This case series details our institution's novel use of Dexmedetomidine sedation in high risk cardiac children, requiring CT angiograms for surgical assessment Methods: A literature search (publication dates up to 26th March 2018) was performed using PubMed, Medline, and the Cochrane Library, using the MESH search terms: 'Dexmedetomidine', 'CT', 'CT Angiogram' and 'paediatric'. All non-human, pre-clinical studies were excluded. The cardiothoracic surgeons and cardiologists at Great Ormond Street Hospital identified patients. Children received a loading dose of 2–3 mcg/kg Dexmedetomidine over 10 min. Once sedated with an appropriate heart rate for the CT coronary imaging, they were scanned. Results: A total of 10 children (range 2 to 15 years of age) received Dexmedetomidine sedation for CT coronary angiography. All children attained a heart rate conducive to imaging (70–80 bpm), whilst maintaining haemodynamic stability. The mean decrease in heart rate from baseline was 28.64% (range: 0–41.67) and mean arterial pressure of 11.86% (range: 23.53–21.25). Discussion: In this case-series, Dexmedetomidine was a safe and effective sedative and had favourable side effects for children undergoing CT coronary angiogram.